Analisis Kinerja Internet Hotspot dengan Menerapkan Bandwidth Management Menggunakan Mikrotik User Manager di Kedai KARMILA - Jauharul Mafakhiri (Teknik Informatika Universitas Pamulang, 2021)
Hotspot networks represent the latest developments in information technology where data exchange is carried out without using cables. Good hostspot network infrastructure will affect the quality of the internet that the user feels when using it. Device such as Access Point is used in a hotspot network that connects users to the Internet. In this study, the implementation of the hotspot network installation consisted of router devices using the Mikrotik RouterBoard 750G with the Mikrotik RouterOS v4.90 next update to v5.20 . Mikrotik device access using applications and user manager access using browser. The result of this research is an effort to control network traffic so that bandwidth is maximized and network performance is better maintained. With the bandwidth management feature, every hotspot service provider can maximize internet usage more effectively.